2021
DOI: 10.1093/schizbullopen/sgab010
|View full text |Cite
|
Sign up to set email alerts
|

Small Words That Matter: Linguistic Style and Conceptual Disorganization in Untreated First-Episode Schizophrenia

Abstract: This study aimed to shed light on the linguistic style affecting the communication-discourse in First Episode Schizophrenia (FES) by investigating the analytic thinking index in relation to clinical scores of conceptual and thought disorganisation (Positive and Negative Syndrome Scale, PANSS-P2 and Thought and Language Index, TLI). Using robust Bayesian modeling, we report three major findings: (1) FES subjects showed reduced analytic thinking, exhibiting a less categorical linguistic style than healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…Contrary to our expectation, we did not find a relationship between semantic similarity and severity of formal thought disorder in this sample of FES. In general, the degree of shared variance between computational linguistic measures and observer-rated formal thought disorder scores have not been consistent 29 , 42 , 52 , 70 72 . In particular, while some sentence level structural measures (e.g., connective use 70 , narrativity and referential cohesion 73 ) relate to thought disorder, the overall shared variance is small for word-level measures 73 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Contrary to our expectation, we did not find a relationship between semantic similarity and severity of formal thought disorder in this sample of FES. In general, the degree of shared variance between computational linguistic measures and observer-rated formal thought disorder scores have not been consistent 29 , 42 , 52 , 70 72 . In particular, while some sentence level structural measures (e.g., connective use 70 , narrativity and referential cohesion 73 ) relate to thought disorder, the overall shared variance is small for word-level measures 73 .…”
Section: Discussionmentioning
confidence: 92%
“…We hypothesize that when faced with the task of describing an unfamiliar concrete referent 52 (a picture), patients with schizophrenia will employ words with a higher probability of semantic co-occurrence. We expect abnormal semantic similarity to be evident in the untreated, first episode phase of illness and relate to formal thought disorder, reduced cognitive control and processing speed in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Parts of speech that are reportedly abnormal in schizophrenia, are not universally present across languages. For example, in psychosis, formal thought disorder in English speakers relates to excess use of pronouns 37 , 38 and discourse connectives 39 , but reduced use of articles and prepositions relative to other function words 40 , 41 . In particular, first person singular pronouns (which by definition excludes referring to the listener) are increased 38 , 42 while first person plural pronouns (which may or may not exclude the listener) are reduced in the presence of psychosis 36 .…”
Section: Sociomarkers Biomarkers and Biosocial Markersmentioning
confidence: 99%
“…Other studies combine clinical findings and a natural language processing (NLP) approach, consisting in a language analysis made by an artificial intelligence which is programmed to understand text and spoken words in a similar way to human beings [ 27 , 28 ]. Silva et al, 2021 [ 29 ], for example, found that people with a first episode of schizophrenia (FES) have a linguistic style characterized by reduced analytic thinking, with less categorical linguistic style (that is with less formal and hierarchical patterns) than healthy controls (HC), but using the same proportion of function (including articles, prepositions, conjunctions, non-referential adverbs, negations, and auxiliary verbs) and content words (words that hold meaning on their own). Disorganization as a clinical item also seems to be related to an aberrant use of connectives (specifically increased temporal but decreased use of causal connectives) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%